2017
DOI: 10.3354/meps12062
|View full text |Cite
|
Sign up to set email alerts
|

Highly localized replenishment of coral reef fish populations near nursery habitats

Abstract: Connectivity is essential for ecosystem functioning, and in particular for the population dynamics of species that use different habitats during consecutive life stages. Mangrove and seagrass habitats serve to replenish populations of a range of species that live on coral reefs, but we know little about the fate of these early stages and the spatial scale at which adult populations benefit from this enhancement effect. We examined densities of 12 ecologically important Caribbean fish species across 3 nursery-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…One potentially counterintuitive result of our study was that most reef fish species were associated with survey sites farther from mangroves, especially given that a recent study found distance from juvenile fish habitats to have a negative effect on offshore fish densities (Nagelkerken et al. ). However, we did not find this result entirely surprising given that several studies have found increased distance from shore to be correlated with increased fish metrics.…”
Section: Discussionmentioning
confidence: 84%
“…One potentially counterintuitive result of our study was that most reef fish species were associated with survey sites farther from mangroves, especially given that a recent study found distance from juvenile fish habitats to have a negative effect on offshore fish densities (Nagelkerken et al. ). However, we did not find this result entirely surprising given that several studies have found increased distance from shore to be correlated with increased fish metrics.…”
Section: Discussionmentioning
confidence: 84%
“…Marine fish nurseries are critical habitats for maintaining ecosystem diversity and productivity because they act as population sources for larger ecosystems via recruitment and replenishment (Beck et al, 2001;Dahlgren et al, 2006;Gillanders, Able, Brown, Eggleston, & Sheridan, 2003;Vasconcelos et al, 2010). For example, mangrove and lagoon nurseries make substantial contributions to adult populations in nearby ecosystems, as they provide productive structural habitats suitable for rapid growth and maturation (Nagelkerken et al, 2017;Tournois et al, 2017). Thus, changes in fish nurseries could have major impacts in larger, adjacent ecosystems.…”
mentioning
confidence: 99%
“…abundance and variety of patch types) and configuration (i.e. the spatial arrangement of habitat patches) has been found to influence fish assemblages in seagrasses (Pittman et al , Gullström et al , Staveley et al ), mangroves (Green et al ) and coral reefs (Dorenbosch et al , Pittman et al , Grober‐Dunsmore et al , Kendall et al , Nagelkerken et al ), highlighting that seascape structure affects fishes at multiple spatial scales across multiple habitats. The structure of spaces between preferred habitat patches (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…unvegetated sand or deep water), sometimes referred to as the matrix, can have profound consequences for connectivity across the seascape by forming barriers that prevent or impede movements for some species (Pittman et al , Turgeon et al , Watling et al , Santos et al ). However, there is still a lack of understanding of how far young post‐settlement (juvenile and sub‐adult) coral reef fishes may disperse within tropical seascapes and at what distances nurseries cease to affect adult communities on coral reefs (Nagelkerken et al ). Few formal tests exist on the decrease of reef fish population replenishment away from nurseries, measured in actual distances or isolation (Huijbers et al , Nagelkerken et al , Gilby et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation